Answer:
-21
Step-by-step explanation:
We are told to find f(x) + g(x) for x= -3. Therefore, we must evaluate f(-3) and g(-3), then add them together.
First, evaluate f(-3).
f(x)=4x-7
To find f(-3), we need to substitute -3 in for x.
f(-3)= 4(-3)-7
Solve according to PEMDAS: Parentheses, Exponents, Multiplication, Division, Addition, Subtraction First, multiply 4 and -3.
f(-3)= -12-7
Next, subtract 7 from -12
f(-3)= -19
Next, find g(-3).
g(x)=2x+4
To find g(-3), substitute -3 in for x.
g(-3)= 2(-3)+4
Solve according to PEMDAS. First, multiply 2 and -3.
g(-3)= -6+4
Next, add -6 and 4
g(-3)= -2
Now, we can add f(-3) and g(-3) together.
f(-3) + g(-3)
f(-3)= -19
g(-3)= -2
-19 + -2
Add
-21
Simple...
you have: -7=c-6
You want to isolate the variable c
-7=c-6
-7=c-6
+6 +6
-1=c
Thus, your answer.
Let's say that y is the weight of the mother and x is the weight of the baby.
We know that the baby is 7437 pounds less than the mother, which means you need to add 7437 pounds to the baby's weight to get the mother's.
We can show it like this:
x+7437=y.
We know what the baby's weight is (1400 lbs), so just sub it in:
1400+7437=y
y=8837 lbs
The mom weighs 8837 pounds.
The answer is <span>$11.43
you type 63.50 into your calculator
then divide it by 100
the times it by 18
and you get 11.43
that is the answer</span>